2008
DOI: 10.1530/eje-07-0632
|View full text |Cite
|
Sign up to set email alerts
|

The effects of endothelial nitric oxide synthase gene polymorphisms on endothelial function and metabolic risk factors in healthy subjects: the significance of plasma adiponectin levels

Abstract: Objective: Genetic variants of the endothelial nitric oxide synthase (eNOS) gene, Glu298Asp and T-786C, have been reported to be associated with cardiovascular disease. Adiponectin is an adipocytederived plasma protein with insulin-sensitizing and vascular protective effects; its levels are typically low in metabolic syndrome. Therefore, eNOS gene polymorphisms may also be associated with specific metabolic profiles, including plasma adiponectin levels and atherogenic lipids. Methods: We evaluated the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
6
27
1
1
Order By: Relevance
“…We demonstrated the importance of the T/C eNOS polymorphism as a risk factor for metabolic syndrome (which includes also T2D). We have confirmed previously published association studies with insulin resistance [51,52], the features of metabolic syndrome [53] and with type 2 diabetes [54]. The genotypic frequency of the I/D ACE polymorphism was found to be significantly different between arterial hypertensive patients and patients without hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated the importance of the T/C eNOS polymorphism as a risk factor for metabolic syndrome (which includes also T2D). We have confirmed previously published association studies with insulin resistance [51,52], the features of metabolic syndrome [53] and with type 2 diabetes [54]. The genotypic frequency of the I/D ACE polymorphism was found to be significantly different between arterial hypertensive patients and patients without hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…These studies include two surveys performed in a Spanish population that found a positive association between NOS3 polymorphisms and MS (19,20), and an Italian population study that found an association with diabetes mellitus type II and insulin resistance (21). Additionally, a positive association between 894G>T polymorphism and MS has been shown in Chinese and Japanese populations (18,22).…”
mentioning
confidence: 99%
“…Além disso, um estudo mostrou aumento nas concentrações plasmá-ticas de LDL-colesterol, LDL-colesterol modificado por malondialdeído (MDA-LDL-C) e níveis de insulina em jejum em indivíduos polimórficos para a posição Glu298Asp do gene da NOS3. Esses autores verificaram também redução das concentrações de HDL-C, apoliproteína I, e consequente redução na vasodilatação dependente de endotélio (31). Assim, parece-nos que o elo comum entre dislipidemia e polimorfismo no gene da NOS3 esteja na posição Glu298Asp, onde o glutamato é substituído pelo aspartato na enzima eNOS, modificando sua atividade enzimática e/ou menor ativação por estímulos físicos, como o shear stress.…”
Section: Associação Entre Genótipo Glu298asp +-786t>c E Aptidão Cardiunclassified